Mechanism-Based Pharmacokinetic–Pharmacodynamic Modeling of the Dopamine D(2) Receptor Occupancy of Olanzapine in Rats - Johnson, Martin (Springer US, 2011)
PURPOSE: A mechanism-based PK-PD model was developed to predict the time course of dopamine D(2) receptor occupancy (D(2)RO) in rat striatum following administration of olanzapine, an atypical antipsychotic drug. METHODS: A population approach was utilized to quantify both the pharmacokinetics and pharmacodynamics of olanzapine in rats using the exposure (plasma and brain concentration) and D(2)RO profile obtained experimentally at various doses (0.01–40 mg/kg) administered by different routes. A two-compartment pharmacokinetic model was used to describe the plasma pharmacokinetic profile. A hybrid physiology- and mechanism-based model was developed to characterize the D(2) receptor binding in the striatum and was fitted sequentially to the data. The parameters were estimated using nonlinear mixed-effects modeling . RESULTS: Plasma, brain concentration profiles and time course of D(2)RO were well described by the model; validity of the proposed model is supported by good agreement between estimated association and dissociation rate constants and in vitro values from literature. CONCLUSION: This model includes both receptor binding kinetics and pharmacokinetics as the basis for the prediction of the D(2)RO in rats. Moreover, this modeling framework can be applied to scale the in vitro and preclinical information to clinical receptor occupancy.